2004
DOI: 10.1093/glycob/cwh068
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of galectin-3 and its ligands by Trypanosoma cruzi infection with modulation of adhesion and migration of murine dendritic cells

Abstract: The impact of a pathogen-induced inflammatory response on dendritic cells (DCs) and on their expression of galectin-3 (Gal-3) was studied on splenic DCs (sDCs) from Trypanosoma cruzi-infected mice. We determined the lectin expression and also presentation of ligands using the labeled galectin as probe. By reverse transcriptase polymerase chain reaction, western blot analysis, quantitative glycocytochemistry, and computer-assisted quantitative microscopy, we demonstrate that, in sDCs from infected mice, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 64 publications
3
53
0
10
Order By: Relevance
“…Galectins, such as galectin-1 and galectin-3, are upregulated after pathogen invasion and may serve as a regulator in innate defense during inflammation (6,8,28,47). In the present study, we show in vivo that galectin-1 was upregulated in mice after influenza virus infection, and its levels positively correlated with viral loads.…”
Section: Discussionsupporting
confidence: 60%
“…Galectins, such as galectin-1 and galectin-3, are upregulated after pathogen invasion and may serve as a regulator in innate defense during inflammation (6,8,28,47). In the present study, we show in vivo that galectin-1 was upregulated in mice after influenza virus infection, and its levels positively correlated with viral loads.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it is possible that the up-regulation of Gal-9 expression in DCs or other cells in response to such factors is responsible for the induction of DC maturation. Recently, Vray et al (45) have shown that Trypanosoma cruzi infection up-regulated the expression of Gal-3 and of its ligands in DCs with functional consequences on their capacities of adhesion and migration, indicating Gal may play important roles in modulation of DCs. Our results suggest that Gal-9 plays an important role not only in innate immunity by modulating granulocyte functions but also in acquired immunity by inducing DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…T. cruzi trypomastigotes (Y strain) were maintained by weekly intraperitoneal inoculation into male BALB/c mice (6 to 8 weeks old; Bantin & Kingman Universal, Hull, Humberside, United Kingdom) with 100 blood form trypomastigotes in 0.2 ml of phosphate-buffered saline (PBS) on day 0. For challenge infections, the Tehuantepec strain of T. cruzi was maintained in mice like the Y strain and used as previously described (13,33,52,53,56).…”
Section: Methodsmentioning
confidence: 99%